2009
DOI: 10.1093/pcp/pcp180
|View full text |Cite
|
Sign up to set email alerts
|

Stomatal Density is Controlled by a Mesophyll-Derived Signaling Molecule

Abstract: Stomata are composed of a pair of guard cells and a pore between them, and their density and positions are regulated by developmental and environmental signals. In a screen in which we overexpressed many genes coding for putative secretory proteins one by one in Arabidopsis, we identified a gene named STOMAGEN, which increases stomatal density when overexpressed. The STOMAGEN gene encodes a small peptide with a putative secretory signal sequence at its N-terminus and is expressed preferentially in mesophyll ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
207
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(223 citation statements)
references
References 26 publications
15
207
0
1
Order By: Relevance
“…The anti-parallel β-sheet is packed with the amino-terminal region, which contains a one-turn 3 10 -helix (residues 10-13), supported by three disulphide bonds, the locations of which (Cys8-Cys41, Cys13-Cys20, and Cys16-Cys43) were identical to those previously obtained by enzymatic digestion and mass spectrometry (MS) 11 . This stomagen core, consisting of the β-sheet and a one-turn 3 10 -helix, does not correspond to a single continuous stretch in the aminoacid sequence; it is separated into N-and carboxy-terminal regions (residues 8-24 and 39-44).…”
Section: Structure Of Stomagensupporting
confidence: 54%
See 1 more Smart Citation
“…The anti-parallel β-sheet is packed with the amino-terminal region, which contains a one-turn 3 10 -helix (residues 10-13), supported by three disulphide bonds, the locations of which (Cys8-Cys41, Cys13-Cys20, and Cys16-Cys43) were identical to those previously obtained by enzymatic digestion and mass spectrometry (MS) 11 . This stomagen core, consisting of the β-sheet and a one-turn 3 10 -helix, does not correspond to a single continuous stretch in the aminoacid sequence; it is separated into N-and carboxy-terminal regions (residues 8-24 and 39-44).…”
Section: Structure Of Stomagensupporting
confidence: 54%
“…The functions of the other members remain unclear. Interestingly, it is currently known that stomagen (EPFL9) acts as a positive regulator [10][11][12] . One of the most intriguing questions in this area is how and why peptides from the same family can produce opposite effects on stomatal density.…”
mentioning
confidence: 99%
“…However, the CHALf proteins are similar in sequence to stomatal regulators EPF1, EPF2, and STOMAGEN Kondo et al, 2009), and CHAL itself was originally identified in a stomatal screen (Abrash and Bergmann, 2010). In overexpression assays, CHAL confers distinct, quantifiable stomatal phenotypes (Abrash and Bergmann, 2010), and Hara et al (2009) report in an EFPL family survey that CLL1 and CLL2 can similarly repress stomatal production.…”
Section: Chal Family Overexpression Phenotypes Are Erf Dependentmentioning
confidence: 99%
“…The EPFLs are small proteins predicted (and in one case, demonstrated) to be processed into ;45-to 75-amino acid long secreted peptides with compact Cys knot structures (Kondo et al, 2009;Sugano et al, 2009). Three members of the gene family, EPF1, EPF2, and EPFL9/STOMAGEN, have clear roles in stomatal development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation